2023
DOI: 10.3390/ijms24065129
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiviral and Anti-Inflammatory Activities of N-Acetylglucosamine: Development of an Alternative and Safe Approach to Fight Viral Respiratory Infections

Abstract: Viral respiratory tract infections (RTIs) are responsible for significant morbidity and mortality worldwide. A prominent feature of severe respiratory infections, such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, is the cytokine release syndrome. Therefore, there is an urgent need to develop different approaches both against viral replication and against the consequent inflammation. N-acetylglucosamine (GlcNAc), a glucosamine (GlcN) derivative, has been developed as an immunomodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…In addition to the mechanistic issue, further studies are mandatory to provide the necessary information on whether BNAG1 and BNAG2 are potential candidates of a viable therapeutic strategy to target inflammation in a variety of pathologies, including but not restricted to joint damages 6 , 7 , inflammatory bowel disease 8 , autoimmune diseases 9 , and viral respiratory infections 10 , 11 . While our experimental data indicated that BNAG1 was more effective than NAG or BNAG2, it would be interesting to investigate if it is also more powerful than glucosamine or other NAG derivatives mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the mechanistic issue, further studies are mandatory to provide the necessary information on whether BNAG1 and BNAG2 are potential candidates of a viable therapeutic strategy to target inflammation in a variety of pathologies, including but not restricted to joint damages 6 , 7 , inflammatory bowel disease 8 , autoimmune diseases 9 , and viral respiratory infections 10 , 11 . While our experimental data indicated that BNAG1 was more effective than NAG or BNAG2, it would be interesting to investigate if it is also more powerful than glucosamine or other NAG derivatives mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…N-acetyl glucosamine (NAG), an acetylated derivative of glucosamine, is an essential component of bacterial and fungal cell walls as well as various human tissues 5 . Due to its low cost, ready availability and less side effects as a natural product and significant anti-inflammatory activity, NAG has attracted much attention as an ideal candidate for the treatment of inflammation-related diseases such as joint damage 6 , 7 , inflammatory bowel disease 8 , autoimmune diseases 9 , and viral respiratory infections 10 , 11 . In particular, many clinical trials on NAG have been performed to treat patients with joint disorders, including arthritic diseases, osteoarthritis, rheumatoid arthritis, cartilage damage, joint injury and degenerative joint disease 5 .…”
Section: Introductionmentioning
confidence: 99%
“…MDCK cells were grown as reported elsewhere [ 50 ]. The Brisbane-like influenza A/H1N1 oseltamivir-resistant virus strain A/Parma/24/09 H1N1 was propagated in 80% confluent MDCK cells as previously described, and viral stocks were stored at −80 °C [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…The viral cytopathic effect (c.p.e.) was measured by MTT assay as reported elsewhere by our laboratory [ 51 ]. Results were expressed as a percentage of c.p.e.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from marketed drugs, many natural molecules have also been studied to treat or manage symptoms of respiratory viral infections. In recent years, studies describing the positive effects of natural products, mainly extracted from plants, in the treatment and healing of various pathologies have been numerous [ 69 , 70 , 71 , 72 ], and also in the field of virology, several phytochemicals and phytocomplexes have been screened to test their effectiveness [ 73 , 74 , 75 ]. Moreover, compounds of natural origin are very well-placed in the drug repositioning strategy, as they are characterized by unique properties due to their various phytochemical composition to which many pharmacological activities are attributed.…”
Section: Treatment Of Respiratory Viral Infectionsmentioning
confidence: 99%